Method of Determination of Law in Bahtsul Masail - Kurniawan, Deden; Maheswari, Adine Alimah (Jurnal Scientia Indonesia, 2021)
The Bahstul Masa'il Forum was formed at the XXVIII congress in Yogyakarta in 1989, aiming to solve and make decisions in various problems that arise in Islamic law. Since the establishment of the forum, the mujtahids began to carry out ijtihad, one of which was also attended by several members or scholars of Islamic organizations, such as Nahdlatul Ulama. This study aims to determine the method of determining the law in Bahstul Masa'il Nahdlatul Ulama, and the effect of the determination of this method on Islamic law in Indonesia. The method used in this research is normative juridical through a legal and conceptual approach. Sources of data used in this study, which is sourced from secondary data through a study of laws and regulations, journals, books, articles, and other sources. In this study, it was found that the method of determining the law used in Bahstul Masa'il Nahdlatul Ulama, which includes the qauliy, ilhaqiy and manhajiy methods, and there is a discussion system model which is divided into three groups that focus on determining a decision for each problem discussed in the discussion. Bahstsul Masa'il, these problems are divided into three categories, namely waqiyah, maudhu'iyah, and qauniyah. Then, regarding the influence of the method of law-making decisions in Bahstsul Masa'il on Islamic law in Indonesia, it depends on how we take the attitude of looking at this point of view.